Federal System and Direct Democracy in Switzerland - Miroslaw Matyja (Polit Journal Scientific Journal of Politics, 2021)
The main aim of this work is to present and analyze the structure and the way of operating of the Swiss instruments of direct democracy, as well as its significance for the country’s development. The Swiss example is the best case of functioning democracy in the world. Throughout the centuries, the Swiss political system has evolved into a mature and efficient democracy. The process of its improvement is still going on. Today, the political system of Switzerland can be described as parliamentary-cantonal. In 1848, the country adopted the Federal Constitution and a system based on referenda, while local issues, such as taxes, judiciary, schooling, police, and welfare were left to the cantons. In 1874, the document was amended and the optional referendum was introduced. In 1891, another amendment cemented the unique system by rooting in strongly in direct democracy. The current constitution of Switzerland was adopted by the majority of voter through a referendum that took place in 1999.